Mainstreaming of climate change risks security through mitigation and adaptation strategies in Nepal - Nepal, Pashupati (Unity Journal, 2020)
A combined effect of high mountains and highly concentrated monsoon rainfall and socio-economic conditions make Nepal a highly vulnerable country to climate change. Whereas Nepal barely shares emissions of Global Greenhouse Gases (0.027%), it is the fourth most vulnerable country in the world due to the effects of climate change. In this context, this paper aims to review the National Climate Change Policy, 2019 to identify the mainstreaming of mitigation and adaptation strategies in response to the climate change for different sectors and cross cutting sectors. Such an important policy document has for the first-time addressed climate change mitigation and adaptation strategies for different sectors and cross-cutting sectors. It has made provision of institutional set-up representing federal, provincial and local levels. Some of the new strategies under this policy include development and expansion of 'payment for ecosystem services', construct pond to collect rain water, make cycle lane in urban roads, increase carbon stocks, and use renewable technologies and manage climate finance. It has given sole responsibilities of functional coordination to the Ministry of Forest and Environment (MoFE) leaving other ministries as passive partners. This can create incoherence between and among the ministries and departments. The policy formulation and institutional set-up need to be complemented by legislation to achieve expected out-puts. Until now, there is not a single legal document in Nepal that exclusively addresses the climate change issue. Therefore, promulgation of Climate Change Act 2019 can resolve the problems of climate change in the spirit of this policy.